ЭФФЕКТИВНОСТЬ ЭСТЕТИЧЕСКОГО ВОСПИТАНИЯ УЧАЩИХСЯ НАЧАЛЬНЫХ КЛАССОВ НА ОСНОВЕ ИННОВАЦИОННЫХ ТЕХНОЛОГИЙ - Куттибекова, Г.Т. (SCIENCE and SOCIETY, 2021)
The article illustrates the content of the model which impact on technology of art pedagogy and art-therapy on success fullness of aesthetic education and art-creative development of young learners.
Keywords: art-pedagogy; art-therapy; aesthetic education; model; principles; criteria; complex approach